Changing rod stiffness to moderate stress of adjacent disc in oblique lumbar interbody fusion - a finite element analysis - Po-Hsin Chou; Jing-Jie Chen; Chen-Sheng Chen; Shih-Tien Wang; Chien-Lin Liu; Shih-Liang Shih (BMC Musculoskeletal Disorders)
Abstract Background OLIF (oblique lumbar interbody fusion) is a minimally invasive surgery to treat spinal instability. However, clinical studies indicated the early degeneration of adjacent segments after surgery. The rod stiffness of OLIF was associated with change at adjacent segments. Therefore, the study aimed to compare the biomechanical effects of OLIF with different rod material properties using the finite element (FE) method. Methods A validated L1-L5 lumbar spine was conducted in the biomechanical analysis using FE software ANSYS. The FE model of OLIF with a rod was created. Current biocompatible materials for the rod of the OLIF model were changed, including titanium alloy (OLIF_Ti), nickel-titanium alloy (OLIF_NiTi), and polycarbonate urethane (OLIF_PCU) rod. Four FE models, consisting of the intact model (INT) and implant models, were created. Hybrid control loads, such as flexion, extension, rotation, and lateral bending, were subjected to four models on the L1 vertebral body. The bottom of the L5 vertebral body was fixed. Results At the surgical level, while compared to the INT model, the OLIF_Ti and OLIF_NiTi model resulted in a ROM reduction of over 40% at least, but the OLIF_PCU changed about 10% in flexion and extension. At adjacent level L2-L3, the FE results indicated that the OLIF_Ti and OLIF_NiTi model increased more stress by about 12% at least than the INT model at the adjacent segment, but it demonstrated that the OLIF_PCU would not result in stress rise at the adjacent level L2-L3 in flexion and extension. Conclusion The study concluded that rod stiffness was associated with change at the adjacent segments. The use of OLIF surgery with PCU rods can minimize the impact of the adjacent segment after lumbar fusion.